A case of scrub typhus requiring maintenance hemodialysis - Dae-Yeon Kim; Hee-Soon Park; Dong-Jae Han; Hyo-Chul Kang; Ji-Hye Lee; Won-Jong Jang; Hyo-Wook Gil; Jong-Oh Yang; Eun-Young Lee; Sae-Yong Hong (The Korean Society of Nephrology, 2013)
Renal failure caused by scrub typhus is known to be reversible. In most cases, renal function is almost fully restored after appropriate antibiotic treatment. A 71-year-old man was diagnosed with scrub typhus complicated by renal failure. A renal biopsy revealed histopathologic findings consistent with acute tubulointerstitial nephritis. Renal function did not improve 18 months after discharge and the patient required continuous hemodialysis. Although severe renal failure requiring dialysis is a rare complication of scrub typhus, we describe a case of scrub typhus requiring maintenance hemodialysis. To the best of our knowledge, this is the first such report.